The economic lessons of the nineteen-thirties - Royal Institute of International Affairs; Arndt, H. W. (London : Frank Cass and Company Limited, 1944)
This title, first written as a report for the Chatham House Committee on Post-War Reconstruction, offers an analytical history of the domestic and external economic policies pursued by the great Western powers during the 1930s. Among the countries covered are the United States, Britain and Germany.
One of a series of studies on post-war economic problems undertaken by the Economic group of the Chatham house Reconstruction committee of the Royal institute. cf. Forward.
Includes bibliographical footnotes and index.
aia 07/05/2018
Loans
Keywords: Economic history; Economic policy